Gong wong sound synthesis using digital filters and applications - Meesawat, Kittiphong (Engineering and Applied Science Research, 2012)
Gong wong is an important instrument in Thai music orchestra bands. Its role is to be the tune keeper of the bands. Thus gong wong sound synthesis could be a key factor in a development of a computer aided Thai music composition. This article presents a gong wong sound synthesis method based on an assumption that the gong sound is a composition of exponential decay sinusoids. The gong sounds frequency components were determined through the power spectrum density (PSD) function using Welch’s periodogram method. The decay rates were measured through the reverberation times (T60) of the gong sounds using Schroeder’s backward integral. The frequencies and the decay rates found from the measurements were used to design infinite impulse response digital filters. Thefilters were designed with an aid of the z – transforms table. These filters were implemented on Chuck programminglanguage which is a real-time audio programming language. The filters were controlled by MIDI messages whichthe computer received from a MIDI keyboard. The synthesized gong satisfied the primary users, a Thai musiccomposer. Keywords: Discrete signal processing, Sound synthesis, Thai music